ANALISIS PENGARUH KUALITAS LAYANAN, CITRA MEREK DAN HARGA TERHADAP LOYALITAS PELANGGAN - Rachmat Hutomo Rambe (2020)
This research is a quantitative study that aims to determine the effect of service quality, brand image and price on customer loyalty. The population in this study were online transportation users of Gojek and Grab motorcycles in Ciputat District. The sample size was taken as many as 100 respondents, with the method of probabilty sampling research that is simple random sampling. Data collection was taken using a questionnaire via Google Form. The data analysis technique used is descriptive analysis and inferential analysis with the analysis tool used is Partial Least Square (PLS). The results showed that (1) service quality had a positive and significant effect on customer loyalty with a path coefficient of 0.218. (2) Brand image has a positive and significant effect on customer loyalty with a path coefficient of 0.446. (3) The price has a positive and significant effect on customer loyalty with a path coefficient of 0.246.